Aplikasi Scoring System Untuk Penentuan Keputusan Kredit Pada BPR DRJ Berbasis Web - David Alfredo Wiejoyo; Silvia Rostianingsih; Lily Puspa Dewi (Jurnal Infra, 2020)
In the banking world, specifically rural bank, lending a credit facility is a crucial business step. To be given a credit facility, the customer first have to pass through several assessment to determine the eligibility wether the customer met to be given a credit facility. Sales or the customer themselves can collect the requirement and sent them to the rural bank to complete the requirement of a credit facility. The assessment will be held by human and tend to have error-prone. Another obstacle is the distance, the customer have to come to the rural bank themselves or even send the requirement which takes time to send the requirement. These obstacles given the writer an idea to create the application. This application created based on web with HTML and PHP language alongside with Javascript features with MySQL database. This application can run the process needed from the beginning of collecting requirement until the score of the assessment is out. The application can aslo store the uploaded documents to the application database.The result of this thesis is the application can run the process of credit scoring until the score is out. The application can also print the required legal documents created by the application. The application can run responsively at different platform. The thesis also meet the problem statement.